Pengaruh Pelatihan dan Pengembangan Karier terhadap Prestasi Kerja Karyawan PT XYZ Teknik - Ririn Uke Saraswati; Ranuyoga Arsyiandi; Muhammad Harun Marifatullah; Naidi Wizaya; Dany Prio Hutomo (Jurnal Riset Akuntansi, 2026)
This study aims to analyze the effect of training and career development on employee performance at PT XYZ Teknik. The study used a quantitative approach with a survey method. The study population was 82 employees, with a saturated sampling technique so that the entire population was sampled. Data were collected through distributing questionnaires that had been tested for validity and reliability, so they were suitable for use as research instruments. Data analysis was carried out using statistical tests, namely the t-test to see the partial effect and the F-test to test the simultaneous effect between variables. The results showed that training had a significant effect on work performance, indicated by a calculated t-value of 3.498 which was greater than the t-table of 1.990 and a significance level of less than 0.05. In addition, career development also had a significant effect with a calculated t-value of 3.448 which was greater than the t-table of 1.990 and a significance level of less than 0.05. Simultaneously, training and career development were proven to have a significant effect on employee performance with a calculated F-value of 206.883 which was greater than the F-table of 3.11. These findings emphasize the importance of implementing structured training programs and ongoing career development to optimally improve employee competency and performance.